تاثير التسويق الداخلي على كفاءات الخدمة المصرفية دراسة حالة بنك الفلاحة و التنمية الريفية بالاغواط - رحمون صبرينة; حجاج هاجر فتيحة; بوخلخال خالد (جامعة عمار ثليجي الاغواط, 2022)
This study aims to find out the role of lslamic banking promotion and its affection on the consumers behavior through the element of promotional mix. ”advertising, personal selling, sales promotion, and public relation". “The case study was carried out at the bank of agriculture and Rural development “Al-Badr” in the wilaya of laghouat. We distributed the questionnaire to a random sample of 100 consumers, where the results of the study shewed that tha premetional mix elements have an effective role in influencing consumer behavior and drawing his attention about Islamic banking services and products at the Bank of Agriculture and Rural. Development “Al-Badr” in the state of laghouat.